Clinical Outcome and Medical Cost of Originator and Generic Antihypertensive Drugs: A Population-Based Study in Yinzhou, China - Huang, Tao; Bai, Lin; Wushouer, Haishaerjiang; Wang, Zhiyuan; Yang, Mingchun; Lin, Hongbo; Shen, Peng; Guan, Xiaodong; Shi, Luwen (Frontiers in Pharmacology, 2022)
Background The substitution of generic drugs can effectively alleviate the rapid growth of drug costs, however, the clinical effectiveness and medical costs between originator products and generics were barely studied in China. Objectives To compare the effectiveness of antihypertensive drugs and hypertension-related medical costs between originator and generic initiators in Yinzhou, China. Methods We conducted a population-based retrospective cohort study using the Chinese Electronic Health Records Research in Yinzhou (CHERRY), from July 1st, 2011 to December 31st, 2018. Hypertension patients initiating with originator products were compared with patients initiating with generic counterparts. We used 1:1 propensity score matching to pair the two groups based on sociodemographic, clinical, and health service utilization variables. Cox proportional regression was adopted to compare the rate of hospitalization for hypertension-related cardiovascular disease between matched originator and generic initiators. Wilcoxon matched-pairs signed-rank test was used to compare annual hypertension-related medical costs. Results 10535 matched pairs of patients were included in the comparative study of originator products and generic, corresponding to seven antihypertensive drugs including amlodipine, felodipine, nifedipine, irbesartan, losartan, valsartan, and metoprolol. The average age of patients included in the analysis was around 60 years (originator vs generics initiators: from 59.0 vs 59.1 years in losartan to 62.9 vs 63.6 years in nifedipine). Higher hospitalization rates among originator initiators were observed for three calcium channel blockers (Hazard ratio[95%CI]: amlodipine, 3.18[1.43, 7.11]; felodipine, 3.60[1.63, 7.98]; and nifedipine, 3.86[1.26, 11.81]; respectively). The remaining four out of seven drugs of the clinical endpoint estimates showed comparable outcomes between originator products and generics (Hazard ratio[95%CI]: irbesartan, 1.19[0.50, 2.84]; losartan, 1.84[0.84, 4.07]; valsartan, 2.04[0.72, 5.78]; and metoprolol, 1.25[0.56, 2.80]; respectively). Higher median annual hypertension-related medical costs were observed in originator initiators (all P < .001), except for metoprolol (P = .646). Conclusions We observed comparable or even better clinical outcomes and less medical cost associated with the use of antihypertensive generics compared to originator counterparts. This could help increase patient and provider confidence in the efficacy of generic medicines to manage hypertension diseases.